BUKU PAL MALETER PAHLAWAN HONGARIA DAN SUBSTANSI NASIONALISME KESEJARAHANNYA - Arafah Pramasto; Sapta Anugrah (Dauliyah Journal of Islamic and International Affairs, 2021)
Hungary had gained attention from international society due to its rejection of Middle Eastern refugees during 2015-2018. The sophisticated progress of information technology easily spreads that news and potentially misused by some extremists. However in History of Hungary a figure named Pal Maleter was martyred for his role against Communism. A book titled ‘Pal Maleter Pahlawan Hongaria’ is the only primary source in Indonesia about him that’s written by ex-wife of the late Pal, Maria Maleter. This research purposed to discover historical nationalism substance of that book. History research’s method is deployed in standardized steps of it such as heuristic or submitting sources, critique to assess sources, interpretation upon collected facts, historiography or historical writing. The research attested that the book consisted three historical nationalism of Hungary such as respect of courage as inherited values from their ancestors, Budapest as capital which symbolizes resistance against foreigners and reciprocal against extraneous thoughts like Pan-Slavism, Nazism, and Communism.